THE DEVELOPMENT OF ATTRACTION POTENCY TO IMPROVE THE QUALITY OF DENPASAR CITY TOURISM - Ni Nyoman Sri Wisudawati; Putu Ratna Juwita Sari; I Made Sindhu Yoga; I Made Mastianta Nadera (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2020)
Purpose: The purpose of this study is identifying and mapping to select pre-existing potential and the management of tourist attraction which have been developed both from attraction and supporting facility on all tourist attraction in Denpasar city. Research methods: This research used qualitative method with technique of participant observation collecting data, comprehensive interviews and documentation. Results and discussions: The results of this research are recommendation of tourist destinations equally considered for development using Integrated Model of the destination competitiveness model created by Dwyer and Kim (2003). The final results of development strategies are based on the analysis of SWOT. Conclusion: In order to be able to focus on the competitiveness of a destination, a macro business perspective is required for the entire tourism industry, meaning that all stakeholders should work with each other by focusing on the common benefits of destination rather than on opportunistic objectives